Kisah Sulaiman A.S Dalam Al-Qur'an - Muhammad, Muhammad Thaib (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2020)
Solomon A.s was a prophet and apostle who was sent to his people with revelations to him like the other apostles. However, he was a king who had a large kingdom, so that many kings submitted to him by paying jizyah to him. Solomon was inspired by Allah Most High's knowledge, ingenuity and good political knowledge. At the beginning of his reign he had built Baitul Maqdis and after that he built a fortress in the city of Yurussalem. In carrying out his reign, Solomon A.s had an army of humans, jinn and animals. During preaching to spread the religion of God Almighty, it is supported by miracles like the other messengers of Allah. He ran his kingdom for forty years. Then at the age of fifty-two he died in a state of worship to Allah SWT in a house of worship. No one knows that Sulaiman A.s has died except after termites eat the stick that he held in his hand. After that the jinn and humans only found out that he had died.